Pandangan Hakim Pengadilan Agama Terhadap Maṣlaḥah - Muslihun Muslihun (Rumah Jurnal Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2020)
Marriage and polygamy dispensation is a regulation contained inLaw No. 1 of 1974 concerning Marriage. In practice, the judges haveseveral considerations, including the consideration of maṣlahah. Thisresearch will discuss about how the judges of the Religious Courts in theCentral Java region understood maṣlaḥah and its implementation inmarriage dispensation and polygamy cases. This is a descriptive-analyticfield research. Data collection using interview techniques. The dataobtained is then analyzed inductively with a normative juridicalapproach. The results of this study are that the perception andimplementation of judges regarding maṣlaḥah in the case of marriageand polygamy dispensations are not in accordance with the provisions ofthe ma teorilaḥah theory compiled by the ulama of fiqh proposal